New insights into interface charge-transfer mechanism of copper-iron layered double hydroxide cathodic electrocatalyst in alkaline electrolysis. Issue 2 (April 2022) - Bhavanari, Mallikarjun; Lee, Kan-Rong; Tseng, Chung-Jen; Su, Bing-Jian; Chen, Jin-Ming; Chang, Jeng-Kuei; Bhattacharyya, Aninda Jiban; Su, Ching-Yuan
Abstract: Transition metal layered hydroxides are potential catalysts for hydrogen evolution reaction (HER) and oxygen evolution reaction in alkaline electrolysis (AE). Recent researches focused on NiFe layered double hydroxide (LDH) as efficient, cost-effective electrocatalyst due to the proton and hydroxide adsorption kinetics by Ni and Fe. However, Cu has been known to exhibit higher adsorption of the proton, thus by replacing Ni with Cu in NiFe LDH shows potential for enhancing the chemical kinetics of HER due to filled d-orbitals and electron transfer. Here, we first demonstrate a strategy of modulating the electronic structure of CuFe LDH, by manipulating Cu/Fe ratio and nanostructure, to improve the HER catalysis of single layer and cost-effective transition metal LDHs in AE. The atomic allocations of Cu and Fe based on the proposed method in the synthesis of LDH allows for optimizing the proton and hydroxide adsorption during electrocatalysis, where the CuFe LDH generate a current density of − 10 mA cm -2 at the overpotential of − 110 mV and a highly enhanced electrolysis stability at − 100 mA cm -2 . Meanwhile, a low overpotential of 257 mV (10 mA cm -2 ) is achieved. Advanced spectroscopic characterizations, including X-ray photoelectron spectroscopy, confirms the electronic structure modulation with adjustment of Cu/Fe ratio; and the synchrotron sourced X-ray absorption spectroscopy unambiguously confirm the higher electron density of Cu and the unique M-O(H)-M ' structure that enhances water splitting by facilitating ion adsorption and electron transfer. The cathodic activation energy of 14.34 kJ mol -1 is achieved by higher electronic density due to electronic modulation of the catalyst structure. This work demonstrates the insights of electronic structure modulation for the rational design of efficient catalysts without noble or rare-earth metals for HER. Graphical Abstract: ga1 Highlights: Efficient charge transfer, proton and hydroxide adsorption in Volmer step boost HER. CuFe LDH accelerate water dissociation in alkaline electrolysis. Electronically modulated CuFe LDH requires − 110 mV at − 10 mA cm -2 . CuFe LDH exhibits Pt-like activity at − 100 mA cm -2 . Activation energy of CuFe LDH for HER is 14.34 kJ mol -1 .